Influence of CAD/CAM Abutment Heights on the Biomechanical Behavior of Zirconia Single Crowns - Jefferson David Melo de Matos; Leonardo Silva Gomes; Nathália de Carvalho Ramos; Daher Antonio Queiroz; João Paulo Mendes Tribst; Tiago Moreira Bastos Campos; Alexandre Luiz Souto Borges; Guilherme da Rocha Scalzer Lopes; Marco Antonio Bottino; Tarcisio José Arruda Paes Junior (Metals, 2022)
The biomechanical behavior of the universal link (titanium base) prosthetic abutment with different heights in implant-supported restorations was evaluated. Forty regular implants (4 × 10 mm) in titanium were used, divided into two groups according to the abutment height (n = 20): 4.5 × 4 mm (short) and 4.5 × 5.5 mm (long). Using CAD/CAM technology, zirconia crowns were milled and cemented onto the prosthetic abutments. Half of the specimens were submitted to the initial maximum fracture load test in a universal testing machine. The long abutments presented fracture load (41.1 ± 6.96 kgf) statistically similar to the short abutments (49.5 ± 7.68 kgf). The other half of the specimens were submitted to mechanical cycling (2,000,000 cycles, 2 Hz with a stainless-steel antagonist with a diameter of 1.6 mm), following ISO 14801:2007. Subsequently, the survival of the specimens was evaluated using the survival analysis function, Kaplan–Meier and Mentel–Cox (log- rank) (p < 0.05). The finite element analysis was performed in similar conditions to those used for the in vitro test through computer-aided engineering software (version 19.2, ANSYS Inc., Houston, TX, USA). The biomechanical behavior of both models was similar regardless of the evaluated structure of the set. It was concluded that both short and long abutment presents promising fatigue behavior and stress distribution for use in long-term implant-supported restorations.